Pengaruh Persepsi Konsumen, Brand Equity Instagram Terhadap Kepuasan Pelanggan Pada Pengguna Fitur Instagram Shopping (Survey Pada Pengguna Aplikasi Instagram Mahasiswa Jurusan Manajemen Angkatan 2018 & 2019 Universitas Islam Malang) - Kharisma M.Haqiqi; M Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine how the influence of consumer perceptions, Instagram Brand equity on customer satisfaction on users of the Instagram shopping feature (Survey on Instagram application users of 2018 & 2019 Management Department Students, Islamic University of Malang). The sample in this study based on Slovin was taken using purposive sampling technique and measured by simple formulas and calculations so that the number of samples was 92 respondents. The data collection method used is the method of distributing questionnaires to respondents. The data analysis technique used in this research is multiple linear regression. The results showed that the variable consumer perception and Brand equity simultaneously had a significant effect on customer satisfaction, the variable consumer perception partially had a significant effect on customer satisfaction and the variable Brand equity had a significant effect on purchasing decisions. Keywords: Perception, Brand Equity, Customer Satisfaction.